2016
DOI: 10.1016/j.appet.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of alcohol use to weight loss in the context of behavioral weight loss treatment

Abstract: Despite common wisdom that reducing alcohol intake will facilitate weight loss, little research has examined whether participants in behavioral weight loss treatments actually decrease their alcohol intake, or whether reduced alcohol intake relates to weight loss outcomes in this context. This study examined the relationship of alcohol use to energy intake excluding alcohol and to weight in 283 overweight and obese adults participating in a 26-session behavioral weight loss treatment. The majority of participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
(60 reference statements)
0
12
1
Order By: Relevance
“…Though the association between alcohol consumption and body weight is unclear, decreasing or eliminating calories from alcohol is typically recommended during weight loss. Despite the potential benefits of reducing alcohol consumption on weight management, few studies have examined whether participants report changes in alcohol intake during weight loss treatment and whether alcohol influences weight loss. One study demonstrated no change in alcohol intake during a lifestyle intervention , while another showed decreased intake at the end of treatment .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the association between alcohol consumption and body weight is unclear, decreasing or eliminating calories from alcohol is typically recommended during weight loss. Despite the potential benefits of reducing alcohol consumption on weight management, few studies have examined whether participants report changes in alcohol intake during weight loss treatment and whether alcohol influences weight loss. One study demonstrated no change in alcohol intake during a lifestyle intervention , while another showed decreased intake at the end of treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential benefits of reducing alcohol consumption on weight management, few studies have examined whether participants report changes in alcohol intake during weight loss treatment and whether alcohol influences weight loss. One study demonstrated no change in alcohol intake during a lifestyle intervention , while another showed decreased intake at the end of treatment . Alcohol intake was not related to weight change but was associated with change in end‐of‐treatment energy intake .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, alcohol consumption was more prevalent in urban populations. Alcohol consumption may lead to overeating episodes and highly impulsive individuals may be [21] b > 80 cm for women and >94 cm for men [22] at risk for increased energy intake during or after episodes of drinking ("binge eating") [24]. Thus, alcohol may contribute to an increase in body weight associated with a certain drinking pattern [33].…”
Section: Discussionmentioning
confidence: 99%
“…age, sex, location of residence, tobacco use, alcohol consumption and use of hormonal contraception) was made in multiple logistic regression analysis. All tests were two-sided and p < 0.05 was considered statistically significant [24][25][26].…”
Section: Discussionmentioning
confidence: 99%